Análise da rentabilidade de empresas privadas de planejamento e assistência técnica na agricultura - Nobre , José Mariano; Paniago , Euter; Batista de Oliveira , Evonir; Coelho de Alvarenga , Sonia; Barbosa , Túlio (Revista Ceres, 2025)
The present study had as its objective analysis of the viability of private firms to furnish technical assistence in the agricultural area. These firms function in essentially the same role as the governamental agricultural extension service (Empresa Brasileira de Assisténcia Técnica e Extensdo Rural — EMBRATER).